2022
DOI: 10.3389/fphys.2022.857853
|View full text |Cite
|
Sign up to set email alerts
|

Acute Endoplasmic Reticulum Stress Induces Inflammation Reaction, Complement System Activation, and Lipid Metabolism Disorder of Piglet Livers: A Proteomic Approach

Abstract: Endoplasmic reticulum stress (ERS) is closely associated with the occurrence and development of many liver diseases. ERS models mostly include experimental animals such as rats and mice. However, pigs are more similar to humans with regards to digestion and metabolism, especially liver construction, yet few reports on ERS in pigs exist. In order to explore changes in the liver under ERS, we used tunicamycin (TM), which can cause liver jaundice and damage liver function, to establish acute ERS models in piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Evidence indicates that the complement cascade, as one of the primary upregulated inflammatory pathways, appears consistently in various neurodegenerative disorders, driving the degeneration progression and cognitive impairment [22]. In tunicamycintreated acute ERS models, the complement system activation product C3 was elevated [21]. Astrocytes regulated C3 secretion via the NF-κB signaling pathway, which was closely related to ERS [23,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that the complement cascade, as one of the primary upregulated inflammatory pathways, appears consistently in various neurodegenerative disorders, driving the degeneration progression and cognitive impairment [22]. In tunicamycintreated acute ERS models, the complement system activation product C3 was elevated [21]. Astrocytes regulated C3 secretion via the NF-κB signaling pathway, which was closely related to ERS [23,59].…”
Section: Discussionmentioning
confidence: 99%
“…Through down-regulation of C3 in vitro, LPS-induced lung cells were able to maintain viability and suppress apoptosis by decreasing ERS expression [20]. In tunicamycin-established acute ERS models of piglets, the complement system was activated, which produced higher levels of activation product C3 [21]. Within the central nervous system, astrocytes are the primary source of the secreted C3, while microglia and neurons express C3aR [22].…”
Section: Introductionmentioning
confidence: 99%
“…Interesting, endoplasmic reticulum stress (ERS) markers were upregulated in pig livers following the LPS challenge, including the receptor protein kinase receptor-like endoplasmic reticulum kinase (PERK), eukaryotic translation initiation factor 2α (eIF2α, also known as EIF2S1 ), the transcription factor C/EBP homologous protein (CHOP), and activating transcription factor 4 (ATF4). Wang et al [ 27 ] demonstrated that acute ERS induces inflammation, complement activation, and lipid metabolism disorder, leading to liver injury in pigs. In human mesangial cells, anti-dsDNA antibodies induced the activation of NF-κB and upregulated the expression of IL-1β and TNF-α, depending on the PERK/ATF4/NF-κB pathway [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, given that C3 is the central component of the complement system, which is activated by the ERS 78 and is highly expressed in AD, 79 Finally, it has been described that accumulating misfolded proteins in the ER can overwhelm the protein quality control, causing cell death in AD. 80 Then, cells can activate the UPR, which mediates cell survival by slowing protein translation 81 and being proapoptotic Bcl-2 proteins overexpressed, leading to the activation of the Caspase cascade, and generating their related breakdown products of α-spectrin such as SBDP 150 and 120.…”
Section: Discussionmentioning
confidence: 99%
“…Then, given that C3 is the central component of the complement system, which is activated by the ERS 78 and is highly expressed in AD, 79 being associated with pathological Aβ aggregation, we evaluated C3 gene expression levels in T/I/C‐activated astrocytes. C3 gene expression in activated astrocytes was about 10x more than the control cells and was completely blocked by UB‐SCG‐51 treatment.…”
Section: Discussionmentioning
confidence: 99%